2014
DOI: 10.3389/fnhum.2014.00431
|View full text |Cite
|
Sign up to set email alerts
|

Reading performance is not affected by a prism induced increase of horizontal and vertical vergence demand

Abstract: Purpose: Dyslexia is the most common developmental reading disorder that affects language skills. Latent strabismus (heterophoria) has been suspected to be causally involved. Even though phoria correction in dyslexic children is commonly applied, the evidence in support of a benefit is poor. In order to provide experimental evidence on this issue, we simulated phoria in healthy readers by modifying the vergence tone required to maintain binocular alignment.Methods: Vergence tone was altered with prisms that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…On the other hand, in our study, the number of regressive saccades was significantly elevated (from 13.2% in steady reading conditions to 18.4% with simulated nystagmus). Whereas the value of 13.2% of regressive saccades under normal reading conditions is in line with or is even rather low compared with the amount of approximately 13–16% reported in the literature [ 27 , 36 , 37 ] or even up to 15–25% according to Rayner et al [ 38 , 39 ], the measured amount during simulated nystagmus lies on the upper bound. Perhaps the moving text may have required subjects to go back and find a word they missed, thus accounting for the increase in regressions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, in our study, the number of regressive saccades was significantly elevated (from 13.2% in steady reading conditions to 18.4% with simulated nystagmus). Whereas the value of 13.2% of regressive saccades under normal reading conditions is in line with or is even rather low compared with the amount of approximately 13–16% reported in the literature [ 27 , 36 , 37 ] or even up to 15–25% according to Rayner et al [ 38 , 39 ], the measured amount during simulated nystagmus lies on the upper bound. Perhaps the moving text may have required subjects to go back and find a word they missed, thus accounting for the increase in regressions.…”
Section: Discussionsupporting
confidence: 86%
“…For statistical analysis, a linear mixed effects model with reading speed (letters per second), saccadic amplitude, saccade count, number of regressive saccades, fixation count, average fixation duration, and maximal fixation duration as dependent variables was used. Reading speed in letters per second was chosen because it applies better to single word reading than words per minute and is consistent with previous reports from us [ 27 , 28 ] and other groups [ 20 , 29 ]. For controls, reading condition (‘steady’ and ‘simulated nystagmus’) was used as the independent variable.…”
Section: Methodsmentioning
confidence: 80%
“…Finally, reading fixation duration was related to symptoms score only. This is in line with previous studies which found no significant effect of binocular coordination aspects on fixation duration (Dysli et al, 2014;Jainta & Joss, 2019;Kirkby et al, 2008); but opposed to , who found an increase of fixation duration for poor vergence adjustments. The relation between objectively measured vergence drift and fixation duration and asthenopic symptoms was further confirmed when objective measures only predicted asthenopic symptoms in this present study.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies assessed optometric measures and binocular parameters during reading and observed the reaction on training . But there are various studies assessing optometric measures or the training of binocular parameters andtheoreticallyrelating them to binocular coordination used for reading without objectively measuring it (Bucci, Kapoula, Brémond-Gignac, & Wiener-Vacher, 2006;Dusek, Pierscionek, & McClelland, 2010;Dysli, Vogel, & Abegg, 2014;Palomo-Álvarez & Puell, 2010;Scheiman et al, 2018). However, some of these studies addressed reading performance taking reading times into account (Dysli et al, 2014) or others related eye movement parameters to optometric parameters (Kapoula et al, 2016;Talasan, Scheiman, Li, & Alvarez, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation